Open innovation community for university-industry knowledge transfer: A Colombian case - Adela M. Vélez-Rolón; Manuel Méndez-Pinzón; Oscar L. Acevedo (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Academia-enterprise collaboration is understood as a determinant that improves innovation and competitiveness. The mechanisms by which this collaboration occurs have awakened increasing interest among academics, as well as in the business sector. This research aims to identify how open innovation communities can mediate the academia-enterprise relationship, as well as the factors that are more affected by this mediation. Based on the literature, the article addresses the definition of open innovation communities (OICs), university-enterprise cooperation, knowledge transfer (KT), as well as an understanding of OICs as a mechanism for academia-enterprise transfer. An analysis of twelve OICs, conformed by professors, students, graduates, and experts from a Colombian higher education institution is performed. For the data analysis, a factor analysis involving structural equation modeling is carried out. Our results highlight the most important characteristics to take into account in the study of knowledge transfer when OICs are involved, and they also indicate the level of connection between these factors.
Keywords: 650; knowledge transfer; knowledge management; open innovation community